INOVASI METODE PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN UNTUK MEMBANGUN KATRAKTER AKTIF DAN KRITIS - Dikarsa, Asep Anggi (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2024)
Citizenship Education (PKn) has an important role in forming the character of the younger generation who are active, critical and have a national perspective. However, the dominant conventional learning methods, such as lectures and memorization, are often less effective in encouraging active student involvement. This research aims to identify and analyze innovative learning methods that can improve students' active character and critical thinking abilities. The research method used is qualitative with a descriptive approach, involving observation, interviews and document analysis in several educational institutions. The research results show that methods such as project-based learning, flipped classes, the use of interactive multimedia, collaborative discussions, and simulations are effective in increasing students' active participation, learning motivation, and analytical abilities. This method is also relevant to the learning needs of the 21st century, which demands collaboration, digital literacy, and contextual problem solving. This research informs innovative integration methods into the Civics curriculum, ongoing teacher training, and the provision of adequate technological infrastructure to support implementation